Socialization of Batik Waste Utilization into Wood Putty - Yunita Pane; Togar Timoteus Gultom; Suhelmi (Universitas Lancang Kuning, 2023)
Batik is also an Indonesian cultural heritage whose manufacturing process uses the method of dyeing cloth with wax to hold the dye. The cloth is coated with wax and then colored. In addition, a lot of batik waste is wasted and causes environmental pollution. This environmental pollution starts from the beginning of the production process, namely the selection of raw materials, wasteful use of raw materials, water, and energy to limited quality in the final stages of the production process which results in an increase in the quantity of failed products. Therefore, the Community Service Team wanted to use the waste generated from the batik production process to be used as wood putty. The socialization and practice held by the community service team can increase the income of the people in the Tanjong Rejo, especially mangrove batik craftsmen.